Graphitic Carbon Nitride (g‐C3N4): An Interface Enabler for Solid‐State Lithium Metal Batteries. (20th January 2020) - Huang, Ying; Chen, Bo; Duan, Jian; Yang, Fei; Wang, Tengrui; Wang, Zhengfeng; Yang, Wenjuan; Hu, Chenchen; Luo, Wei; Huang, Yunhui
Abstract: Solid‐state Li metal batteries (SSLMBs) have attracted considerable interests due to their promising energy density as well as high safety. However, the realization of a well‐matched Li metal/solid‐state electrolyte (SSE) interface remains challenging. Herein, we report g‐C3 N4 as a new interface enabler. We discover that introducing g‐C3 N4 into Li metal can not only convert the Li metal/garnet‐type SSE interface from point contact to intimate contact but also greatly enhance the capability to suppress the dendritic Li formation because of the greatly enhanced viscosity, decreased surface tension of molten Li, and the in situ formation of Li3 N at the interface. Thus, the resulting Li‐C3 N4 |SSE|Li‐C3 N4 symmetric cell gives a significantly low interfacial resistance of 11 Ω cm 2 and a high critical current density (CCD) of 1500 μA cm −2 . In contrast, the same symmetric cell configuration with pristine Li metal electrodes has a much larger interfacial resistance (428 Ω cm 2 ) and a much lower CCD (50 μA cm −2 ). Abstract : Kompatible Schnittstellen : Aus Li und g‐C3 N4 wurde eine Granat‐kompatible Li‐C3 N4 ‐Kompositanode mit einer Li3 N‐reichen Oberfläche synthetisiert. Die Verbundelektrode ermöglicht einen niedrigen Grenzflächenwiderstand und eine hohe kritische Stromdichte für Lithium‐Metall‐Festkörperbatterien.